PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 5 KUPANG - Marlis Evalien Erlinda Para; Fathorrahman Fathorrahman; Dany M. Handarini (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the influence of transformational leadership style, work discipline, and work environment on teacher performance at SMPN 5 Kupang. Method: This study uses a quantitative approach with a survey method. The study population is all 56 teachers with PNS and PPPK status at SMP Negeri 5 Kupang, with a sampling technique using saturated sampling. Data were collected through a Likert-based questionnaire and analyzed using multiple linear regression. Results: (1) The study shows that partially the transformational leadership style does not have a positive and significant effect on teacher performance; (2) Work discipline has a positive and significant effect on teacher performance; (3) The work environment has a positive and significant effect on teacher performance; (4) Simultaneously, transformational leadership style, work discipline, and work environment have a significant effect on teacher performance at SMP Negeri 5 Kupang. Novelty: This study confirms that the improvement of teacher performance is more influenced by internal factors and work environment conditions than the direct influence of transformational leadership style. This finding provides an understanding that transformational leadership plays a role as a supporting factor that strengthens the effectiveness of work discipline and work environment in improving teacher performance.